Advertisement Remove all ads

Let X1, X2, ..., Xn Be Values Taken by a Variable X and Y1, Y2, ..., Yn Be the Values Taken by a Variable Y Such Yi = Axi + B, I = 1, 2,..., N. Then, (A) Var (Y) = A2 Var (X) (B) Var (X) = A2 Var (Y) - Mathematics

MCQ

Let x1x2, ..., xn be values taken by a variable X and y1y2, ..., yn be the values taken by a variable Y such that yi = axi + bi = 1, 2,..., n. Then,

Options

• Var (Y) = a2 Var (X)

• Var (X) = a2 Var (Y)

•  Var (X) = Var (X) + b

• none of these

Advertisement Remove all ads

Solution

Var (Y) = a2 Var (X)

$\text{ Var } (X) = \frac{\sum^n_{i = 1} ( x_i - \bar{X}^{} )^2}{n} \text{ where Mean } \left( X \right) = \frac{\sum^n_{i = 1} x_i}{n}$

$\text{ Var } (Y) = \frac{\sum\nolimits_{i = 1}^n ( y_i - Y )^2}{n} \text{ and } Y = \frac{\sum^n_{i = 1} y_i}{n}$

$\text{ We have } ,$

$y_i = a x_i + b$

$Y = \frac{\sum\nolimits_{i = 1}^n y_i}{n}$

$= \frac{\sum\nolimits_{i = 1}^n a x_i + b}{n}$

$= \frac{a \sum\nolimits_{i = 1}^n x_i}{n} + \frac{nb}{n}$

$= aX + b$

$\text{ Var } (Y) = \frac{\sum^n_{i = 1} \left( y_i - Y \right)^2}{n}$

$= \frac{\sum^n_{i = 1} \left\{ a x_i + b - \left( aX + b \right) \right\}^2}{n}$

$= \frac{\sum^n_{i = 1} (a x_i - aX )^2}{n}$

$= a^2 \frac{\sum^n_{i = 1} ( x_i - X )^2}{n}$

$= a^2 \text{ Var } (X)$

Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 32 Statistics
Q 11 | Page 51
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications

Forgot password?